2005
DOI: 10.1158/0008-5472.can-04-3303
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Transporter ABCG2 Prevents Tumor Cell Death Induced by the Epidermal Growth Factor Receptor Inhibitor Iressa (ZD1839, Gefitinib)

Abstract: Iressa (ZD1839, Gefitinib), used in clinics to treat non-small cell lung cancer patients, is a tyrosine kinase receptor inhibitor that leads to specific decoupling of epidermal growth factor receptor (EGFR) signaling. Recent data indicate that Iressa is especially effective in tumors with certain EGFR mutations; however, a subset of these tumors does not respond to Iressa. In addition, certain populations have an elevated risk of side effects during Iressa treatment. The human ABCG2 (BCRP/MXR/ABCP) transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
139
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 48 publications
1
139
1
Order By: Relevance
“…These results suggest that, as discussed above for imatinib, gefitinib might also have a narrow window, especially in a low concentration range, where its active transport by BCRP is efficient. Consistent with gefitinib being a BCRP substrate, BCRP-transduced A431 cells were resistant to gefitinib compared with the parental cell line (Yanase et al, 2004;Elkind et al, 2005) and the resistant phenotype was reversed by the BCRP-specific inhibitor Ko143 (Elkind et al, 2005). Of note, consistent with EGFR amplification and dependence on EGFR signalling for survival, A431 cells are highly sensitive to gefitinib, with IC 50 values in the nanomolar range.…”
Section: Gefitinibmentioning
confidence: 81%
See 3 more Smart Citations
“…These results suggest that, as discussed above for imatinib, gefitinib might also have a narrow window, especially in a low concentration range, where its active transport by BCRP is efficient. Consistent with gefitinib being a BCRP substrate, BCRP-transduced A431 cells were resistant to gefitinib compared with the parental cell line (Yanase et al, 2004;Elkind et al, 2005) and the resistant phenotype was reversed by the BCRP-specific inhibitor Ko143 (Elkind et al, 2005). Of note, consistent with EGFR amplification and dependence on EGFR signalling for survival, A431 cells are highly sensitive to gefitinib, with IC 50 values in the nanomolar range.…”
Section: Gefitinibmentioning
confidence: 81%
“…Most likely, the apparent discrepancy in these results is due to the selected concentrations of gefitinib used in the different studies. Elkind et al (2005) showed that low concentrations of gefitinib (o1 mM) significantly activated BCRP-ATPase activity in isolated membranes of BCRP-expressing mammalian MCF-7/MX and A431 cells, whereas higher concentrations (41 mM) had a markedly lower stimulatory effect. Consequently, this might explain the lack of gefitinib transport into vesicles of PC-6/SN2-5H cells, since a gefitinib concentration of 30 mM was used in this study (Nakamura et al, 2005).…”
Section: Gefitinibmentioning
confidence: 98%
See 2 more Smart Citations
“…Shorter CA repeat lengths were associated with poorer survival in the absence of therapy with an EGFR TKI, which is a reversal of expectations in TKI-treated patients (Dubey et al, 2006). The multidrug transporter ABCG2 was shown to be active in removing gefitinib from cells (Elkind et al, 2005). In published reports, ABCG2 polymorphisms have been identified as being associated with increased EGFR TKI concentrations, toxicity or both, in patients treated with gefitinib and erlotinib (Cusatis et al, 2006;Li et al, 2007;Rudin et al, 2008).…”
Section: Genetic Polymorphisms and Egfr-targeted Drugsmentioning
confidence: 99%